G514(P) A national study day for junior paediatricians interested in a career in paediatric palliative medicine: A valuable opportunity for networking and career advice in addition to learning. (27th April 2016) - Hills, M; Brook, L; Carragher, P
Abstract : Aims: To assess the appetite and usefulness of a national study day for all British trainee doctors with an expressed interest in paediatric palliative medicine (PPM) either as a specialist or as a paediatrician with a special interest. Methods: Trainees known to the Royal College of Paediatrics and Child Health PPM College Specialty Advisory Committee (CSAC) were emailed and invited to a one day study day at Martin House Children's Hospice. The day was facilitated by three consultants from the Association of Paediatric Palliative Medicine, two of whom are on the CSAC. The day was designed to enhance knowledge, skills and attitudes through talks, workshops and role-play. Trainees were invited to give presentations. Email responses and post course feedback forms were evaluated to assess the perceived usefulness of the day. Results: Of 26 trainees invited, 8 accepted (31%) and 6 attended (23%). Only one trainee offered to present (one of the two with exceptional circumstances for dropping out). Attendees gave universally positive feedback and gratitude. They highlighted the usefulness of specialised teaching, practical workshops and scenarios. Trainees also valued the opportunity to discuss careers (including educational and training opportunities) and to network with their peers. Of the trainees who declined places there was keen interest to be invited in future but there were difficulties getting leave and getting to a Northern venue. Conclusions: Despite reticence to contribute to the programme and difficulties attending the day, trainees found a national PPM study day valuable for: Specialist PPM teaching A career forum Networking These study days will continue to be run twice a year in varied locations around the UK and we welcome trainees interested in PPM.